Penerapan Pembelajaran hifz al Nafs Berbasis Maqashid al Syari’ah di Pondok Pesantren Malang - Husni, Muhammad; Sunhaji, Ahmad (Proceedings of Annual Conference for Muslim Scholars, 2023)
The application of student learning, when viewed from the perspective of maqashid al-syari'ah at the level of human needs in the context of students, namely eating, drinking, exercising and maintaining cleanliness, are included in the primary category (dlaruriyat), while eating three times and exercising twice a week is included in secondary needs. (hajiyat) Alternatively, it can be called tertiary needs (tahsiniyat). Among these learning activities were carried out at the Pondok Pesantren Shirothul Fuqoha' Salafiyah. This research aims to determine the application of hifz al nafs learning based on maqashid al-syari’ah at the Pondok Pesantren Shirothul Fuqoha' Salafiyah in Malang. This research uses descriptive qualitative methods. Observation, interviews and documentation carried out data collection. The source of research data in this study is the manager in the sense of the administrator of the Pondok Pesantren Shirothul Fuqoha' Salafiyah of Malang. The results of this research at the Pondok Pesantren Shirothul Fuqoha' Salafiyah of Malang. have been running in accordance with the theory contained in the maqashid al-syari’ah, namely hifz al nafs in the form of Pondok Pesantren meals, daily and weekly picketing, the existence of health post facilities, then sports and gymnastics. This learning activity is carried out using a direct learning model and regular habituation so that the students get used to these activities, which are included in the context of protecting their souls and those of others.